2023
DOI: 10.3389/fpls.2023.1304627
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with a microbial consortium increases soil microbial diversity and improves agronomic traits of tomato under water and nitrogen deficiency

Valerio Cirillo,
Ida Romano,
Sheridan L. Woo
et al.

Abstract: Microbial-based biostimulants, functioning as biotic and abiotic stress protectants and growth enhancers, are becoming increasingly important in agriculture also in the context of climate change. The search for new products that can help reduce chemical inputs under a variety of field conditions is the new challenge. In this study, we tested whether the combination of two microbial growth enhancers with complementary modes of action, Azotobacter chroococcum 76A and Trichoderma afroharzianum T22, could facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…He et al [37] reported that three species of Bacillus and one of Pseudomonas, inoculated either individually or in co-culture, promoted the growth and the uptake of N-depleted fertilizer of tomato plants, and co-inoculation with more microorganisms with complementary modes of action exerted an additive effect of growth promotion. Recently, Cirillo et al [38] showed how the simultaneous application of Trichoderma afroharzianum and Azotobacter chroococcum enhanced yield and alleviated the effects of combined water-nitrogen stress in tomato. Furthermore, the use of a plant-based biostimulant (sugar cane molasses with yeast extract by yeast autolysis) improved plant performances and fruit quality in tomato-grown plastic tunnels in Southern Italy at summer elevated temperatures [39].…”
Section: Discussionmentioning
confidence: 99%
“…He et al [37] reported that three species of Bacillus and one of Pseudomonas, inoculated either individually or in co-culture, promoted the growth and the uptake of N-depleted fertilizer of tomato plants, and co-inoculation with more microorganisms with complementary modes of action exerted an additive effect of growth promotion. Recently, Cirillo et al [38] showed how the simultaneous application of Trichoderma afroharzianum and Azotobacter chroococcum enhanced yield and alleviated the effects of combined water-nitrogen stress in tomato. Furthermore, the use of a plant-based biostimulant (sugar cane molasses with yeast extract by yeast autolysis) improved plant performances and fruit quality in tomato-grown plastic tunnels in Southern Italy at summer elevated temperatures [39].…”
Section: Discussionmentioning
confidence: 99%
“…Plant Growth Promoting bacteria (PGPB) are eco-friendly, low-cost natural resources that can be integrated to reduce the toxic effects of synthetic inputs and promote sustainable agriculture. PGP bacteria include different genera such as Agrobacterium, Rhizobium, Azospirillum, Azotobacter, Bacillus , and Pseudomonas ( Boleta et al., 2020 ; Rosa et al., 2022 ; Tounsi-Hammami et al., 2022 ; Cirillo et al., 2023 ; Gen-Jiménez et al., 2023 ). These bacteria can act as biofertilizers through various mechanisms, including nitrogen fixation, nutrient solubilization, ammonium production, siderophore production and hormone production.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 'microbial inoculants' constitute a main strategy that inoculates specific beneficial microbiomes to the root zone to boost growth, nutrient, and stress tolerance in tomato plants [34]. Another tactic is engineering microbial consortia, which support plant health and provide disease resistance to root pathogens [35,36]. 'Biofertilizers' refer to the use of beneficial bacteria in tomato seeds, which promote plant growth [37].…”
Section: Introductionmentioning
confidence: 99%